Characterization and comparison of SiC Schottky and Ultra-fast Diodes in a Hard-Switching Buck Converter. - Libby, Rochie Ligaya S. (Philippine Engineering Journal)
This research investigates the impact of the superior switching behavior of the SiC Schottky diode on the efficiency of a hard switching buck converter. The outstanding characteristics of the SiC Schottky diode include high reverse voltage capability, absence of reverse recovery at turn-off, and a switching behavior independent to temperature, which find significant use in power electronics applications demanding fast switching frequencies and high converter efficiency. For benchmarking, we compare the performances of the SiC Schottky diode to a leading ultra-fast diode of comparable rating in a hard switching buck converter with the load current, input voltage, switching frequency and diode turn-off dI/dt as the variable parameters. The important measurements include the diode and the FET switching and conduction losses as well as the buck converter efficiency trends with increasing load current, input voltage, switching frequency and diode turn-off dI/dt.